The earliest long-distance obsidian transport: Evidence from the ∼200 ka Middle Stone Age Sibilo School Road Site, Baringo, Kenya. Issue 103 (February 2017) - Blegen, Nick
Abstract: This study presents the earliest evidence of long-distance obsidian transport at the ∼200 ka Sibilo School Road Site (SSRS), an early Middle Stone Age site in the Kapthurin Formation, Kenya. The later Middle Pleistocene of East Africa (130–400 ka) spans significant and interrelated behavioral and biological changes in human evolution including the first appearance of Homo sapiens . Despite the importance of the later Middle Pleistocene, there are relatively few archaeological sites in well-dated contexts ( n < 10) that document hominin behavior from this time period. In particular, geochemically informed evidence of long-distance obsidian transport, important for investigating expansion of intergroup interactions in hominin evolution, is rare from the Middle Pleistocene record of Africa. The SSRS offers a unique contribution to this small but growing dataset. Tephrostratigraphic analysis of tuffs encasing the SSRS provides a minimum age of ∼200 ka for the site. Levallois points and methods of core preparation demonstrate characteristic Middle Stone Age lithic technologies present at the SSRS. A significant portion (43%) of the lithic assemblage is obsidian. The SSRS obsidian comes from three different sources located at distances of 25 km, 140 km and 166 km from the site. The majority of obsidian derives from the farthest source, 166 km to the south of the site. The SSRS thus provides important new evidence that long-distance raw material transport, and the expansion of hominin intergroup interactions that this entails, was a significant feature of hominin behavior ∼200 ka, the time of the first appearance of H. sapiens, and ∼150, 000 years before similar behaviors were previously documented in the region.